Bleaching of SeaCell (R) Active Fabrics with Hydrogen Peroxide - GÜLTEKİN, BEKİR CENKKUT (KOREAN FIBER SOC, 2016)
Seaweed-based SeaCell (R) fibres have been considered as new materials for textile industry. In this study, seaweedbased SeaCell (R) Active fibres which have antifungal and antibacterial activity have been used. Simple, economic and green process is applied to investigate the bleaching performance of SeaCell (R) Active fabric. Bleaching process has been performed in a laboratory scale dyeing machine by using H2O2 at different concentrations. Also, different bleaching trials were carried out by varying temperature, pH and process duration. Colour Measurements of the bleached SeaCell (R) Active fabrics have been characterized by utilizing Datacolor SF 600 +. Tristimulus and Whiteness Index values have been calculated according to the CIELab system with D65/10 o observer values. After the bleaching treatment, the obtained results reveal that SeaCell (R) Active fabric with satisfactory whiteness index and improved lightness (L*) value can be obtained by processing the fabric at 90 degrees C for 60 min in a bleaching bath with fixed pH 7.5 containing 30 ml/l H2O2. SEM images of untreated and bleached SeaCell (R) Active fabrics also show that some fibres have been damaged after bleaching process.
Keywords: Whiteness; Bleaching; SeaCell (R) fabric; Antimicrobial fibres; Colour measurements